The effectiveness of cognitive behavioral therapy on treatment-resistant depression - Sadrmohammadi, Rezvan; Gholamrezaei, Simin; Ghadampour, Ezatolah (Chronic Diseases Journal, 2020)
BACKGROUND: Treatment-resistant depression (TRD) is a severe and chronic form of major depression. It poses significant clinical, personal, and economic burden and does not respond to antidepressants. Psychotherapy can be a suggested option. The aim of this study was to survey the effectiveness of cognitive behavioral therapy (CBT) on patients with TRD. METHODS: The present study was a quasi-experimental study with pretest, posttest, and follow-up. The statistical population included patients with TRD in Rafsanjan City, Iran, in 2018. 30 subjects were randomly selected and placed into experimental and control groups. Data were collected by Beck Depression Inventory (BDI), Rumination Questionnaire, and Brunel Mood Scale (BRUMS). To analyze data, multivariate analysis of covariance (MANCOVA) was used with SPSS software. RESULTS: CBT led to reducing depression and rumination and improving mood and this outcome was better than control group (P < 0.05). CONCLUSION: TRD is a chronic and disabling disorder that little research has been done about its treatment. CBT can be a good treatment offer for TRD.